The effect of active range of motion exercise on foot sensitivity in type II diabetes mellitus patients - Erliana Dwi Retna Asih; Agung Widiastuti; Mursudarinah (Physical Therapy Journal of Indonesia, 2024)
Background: Diabetes Mellitus (DM) is a metabolic disease that can be characterized by the presence of high sugar levels in the blood, resulting in an imbalance between insulin demand and production in the human body. One of the complications is peripheral neuropathy nerve damage, which causes diabetic ulcers, so there is a risk of decreased sensitivity to diabetics. Active Range of Motion (ROM) exercises are one effort to overcome this. The objective is to determine whether the active ROM of the lower extremities affects foot sensitivity in type II DM patients. Methods: The research used a pre-experimental quantitative research design with the one-group pre-test and post-test method. The sampling technique used purposive sampling with 22 respondents. Results: The analysis using the Wilcoxon test obtained a p-value <0.005. This indicates an increase in foot sensitivity in type II DM patients. Conclusion: There is an effect of active foot ROM on foot sensitivity in type II DM patients.